Magnetoresistance and magnetic susceptibility of doped Si-Ge whiskers - Druzhinin, A.A.; Ostrovskii, I.P.; Kogut, Yu.R.; Warchulska, J.K. (Functional Materials, 2007)
The magnetoresistance and magnetic susceptibility (MS) of Si—Ge whiskers have been determined in the temperature range 4.2-300 K in magnetic fields up to 140 and 4.0 kOe, respectively. The results obtained show two peculiarities: a substantial paramagnetic contribution to the whisker MS and magnetization, non-linear dependency of magnetization on magnetic field. These facts indicate the existence of antiferromagnetic ordering in the whiskers. The magnetization hysteresis really observed at 4.2 K confirms the above supposition. Possible reasons of the effect revealed are discussed.